Properties of black carbon and other insoluble light-absorbing particles in seasonal snow of northwestern China - Pu, Wei; Wang, Xin; Wei, Hailun; Zhou, Yue; Shi, Jinsen; Hu, Zhiyuan; Jin, Hongchun; Chen, Quanliang (The Cryosphere, 2017)
A large field campaign was conducted and 284 snow samples were collected at 38 sites in Xinjiang Province and 6 sites in Qinghai Province across northwestern China from January to February 2012. A spectrophotometer combined with chemical analysis was used to measure the insoluble light-absorbing particles (ILAPs) and chemical components in seasonal snow. The results indicate that the cleanest snow was found in northeastern Xinjiang along the border of China, and it presented an estimated black carbon (CBCest) of approximately 5 ng g−1. The dirtiest snow presented a CBCest of approximately 450 ng g−1 near industrial cities in Xinjiang. Overall, the CBCest of most of the snow samples collected in this campaign was in the range of 10–150 ng g−1. Vertical variations in the snowpack ILAPs indicated a probable shift in emission sources with the progression of winter. An analysis of the fractional contributions to absorption implied that organic carbon (OC) dominated the 450 nm absorption in Qinghai, while the contributions from BC and OC were comparable in Xinjiang. Finally, a positive matrix factorization (PMF) model was run to explore the sources of particulate light absorption, and the results indicated an optimal three-factor/source solution that included industrial pollution, biomass burning, and soil dust.